Do not go gentle into that good night: The European Union's and China's different approaches to the extraterritorial application of artificial intelligence laws and regulations - Wang, Yan (Computer law & security review, 2024)
The extraterritorial application of artificial intelligence (AI) laws and regulations is a form of global AI governance. The EU and China serve as two different examples of how to achieve the extraterritorial applicability of AI laws and regulations. The former shows an explicit territorial extension with more trigger factors, whereas the latter shows vertical regulation with a narrower territorial scope. Both countries’ legislative motivations differ but also have some commonalities. One of the primary goals of extraterritorial application of domestic laws is to protect citizens within their territory. The digital economy's characteristics make it necessary for AI laws to have extraterritorial effects. Without international conventions or treaties, there is a legal vacuum in AI regulation. Additionally, the extraterritorial application of AI laws and regulations helps a state become a global standard-setter and gain an international sphere of influence. However, the extraterritorial application of AI laws and regulations sometimes functions as a form of legal imperialism. This exacerbates the injustice between great powers and weak countries in AI competition. To justify the legitimacy of the extraterritorial application of AI laws and regulations, it is beneficial to adopt the ‘inner morality of extraterritoriality’, a theoretical framework proposed by Professor Dan Svantesson. In fact, extraterritorial applicability depends on the market size and attractiveness. For other countries, whether their AI laws and regulations are endowed with extraterritorial effects is their prerogative. However, they should consider their soft power before implementing legislation.